Detection of microsporidia in local HIV-positive population in Malaysia - Lono, A.; Kumar, S.; Chye, T.T. (2011)
The HIV-positive population, clue to their immuno-compromised nature, is considered more susceptible to parasitic infections than other populations. However despite the reports of other opportunistic pathogens such as Cryptosporidium and tuberculosis reported in vulnerable communities, microsporidia have not been highlighted in the local HIV-positive population in Malaysia. This study aimed to provide preliminary information on the prevalence of microsporidia in the local HIV-population. Microsporidia were detected in 21/247 (8.5) stool samples from the HIV-infected individuals, a significantly higher (P-value <0.05) prevalence than in the control group, in which 5/173 (2.9) were positive. HIV patients were 3x more at risk for acquiring microspordium (OR: 3.12: 95 CI 1.15-8.44). Spores were ellipsoid in shape with outlines that stained dark pink with the interior a lighter shade. Approximately 21 of the positive specimens were from individuals in the 40-49 years age group. Ten individuals who were positive for microsporidia were also positive for other enteric parasites such as Blastocystis hominis and Giardia lamblia. We detected Encephalitozoon intestinalis DNA following nested PCR from three of 10 samples analysed, as demonstrated by an amplicon of 370 bp. From the findings reported, it appears that microsporidial infection in humans may actually be more common than reported. We strongly advocate greater emphasis on personal hygiene through public education on personal hygiene and the consumption of boiled or filtered water. Crown Copyright (C) 2011 Published by Elsevier Ltd on behalf of Royal Society of Tropical Medicine and Hygiene. All rights reserved.